A Survey Of The Motivation Of Exercising For The Santri Putra Pondok Pesantren Sabillurrosyad Gasek Malang 2019 - Defa Dian Dwi Pramuda; Sapto Adi; Olivia Andiana (Jurnal Sport Science, 2022)
The importance of the community to do sports viewed from various aspects and interests. The benefits of sports social good and others are. In terms of physiological, exercise can accelerate the development of the body better, activate and strengthen different types of muscles, the vital capacity, generally tend to realize the development of the organs of the body in a harmonious and functional, in terms of the social sports can trigger strap, the brotherhood of the group, fostering a great responsibility to be affection and respect among fellow.  From the standpoint of sports psychology, the belief that God is the Helper self help athletes through many avenues. First, belief in God fosters self-confidence (confidence) and hope to win (winning expectancy). Efforts to memasyaratkan sports and exercise your community needs to be improved, because by exercising each individual will get an alternative that provides a significant contribution to the achievement of the quality of life of the elderly successful. Then that sport is very recommended because with sports, there are a variety of motion analysis such as: strength, speed, agility, balance, endurance, coordination, flexibility, and stamina, and all it will increase all the quality of function of the organs towards which is better. Boarding school Sabilurrosyad is a place for a muslim who want to explore the science of religion. With the material learning to be focused in the context of religious activities. Sports is considered as an activity that is not so important and also receive less attention of the caretaker cottage. He considers sports activities not too important impact to the lack of allocation of time given to the caretaker cottage to the activities of the exercise. With so these students can not do activity sports freely and maximal. The purpose of this study was to determine how the motivation to exercise santri putra Pondok Pesantren Sabilurrosyad Gasek Malang in the year of 2019. This study uses a research design descriptive quantitative. With a purpose to describe a symptom, events, and happenings that occur in a factual, systematic, and accurate. With a total population of 30 santri putra pondok Pesantren Sabilurrosyad Gasek Malang randomly selected or random sampling, each respondent is not given a certain criteria. The Data from this research is a description of how the motivation to exercise santri putra Pondok Pesantren Sabilurrosyad Gasek Malang. The instruments used to collect data in the form of a questionnaire questionnaire given to each respondent. Techniques of data collection using questionnaires, documentation, and observation. The results of research conducted with 30 respondents, namely santri putra Pondok Pesantren Sabilurrosyad Gasek Malang obtained data showed that motivation to exercise santri putra pondok pesantren Sabillurrosyad Gasek Malang the majority in the category of very high, as is evident by the percentage of the results of the study showed a figure of 60% of 30 respondents have a very high motivation, whereas the remaining 40% of the respondents have the motivation to exercise high. It can be concluded that the motivation to exercise mawlaya Boarding school Sabilurrosyad Gasek Malang 2019 the majority in the category of very high.